REPRESENTASI KARAKTER TOKOH DALAM CERPEN RUSA-RUSA MASUK KACA KARYA MOSTHAMIR THALIB: PENDEKATAN SEMIOTIK CHARLES SANDERS PEIRCE - Sum, Tengku Muhammad (Universitas Lancang Kuning, 2019)
This research has been motivated by literature as reflection of reality. The story ”Rusa-Rusa Masuk Kaca” is selected because the character in the story presents reality. The study of this story uses Charles Sanders Peirce’s semiotic analysis. Namely sign, object, and interprentrant. Semiotic analysis is used to analyze character representation that connect literary work with reality. The method used is qualitative descriptive with a literature study of data collection techniques. Keywords: Short Stories Rusa-Rusa Masuk Kaca, Semiotic Peirce, Character Representation.